MORPHOLOGY AND CELL BIOMASS OF SPONGE Aaptos aaptos AND - Meutia Samira Ismet; Dedi Soedharma; Hefni Effendi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
Aaptos aaptos and Petrosia sp. sponges are known for their ability to produce potential marine bioactive compound. As a metazoan animal with simple body structure, the morphology and it association with symbiont-bacteria could influence their bioactive compound both type and activity, as much as their habitat adaptation. In order to determine morphology and its cell biomass of Aaptos aaptos dan Petrosia sp., samples were taken from the West Pari Island, at 7 m depth. Preserved samples (in 4% formaldehyde) were examined using a histological mounting and centrifugation method to separate the cells fraction of sponge’s tissues. A. aaptos sponge has a soft body structure with 55.9% skeleton-forming fraction, 14.2% sponge cell fraction and 29.9% bacteria fraction. Meanwhile, Petrosia sp. sponge has a rigid body with dominant skeleton-forming fraction (68.6%), and lesser sponge cell and bacteria associated (19.7% and 11.7%, respectively).Keywords: A. aaptos, Petrosia sp, morphology, cell biomass